Post-translational modifications of beta-amyloid modulate its effect on cell mechanical properties and influence cytoskeletal signaling cascades - Varshavskaya, Kseniya B.; Barykin, Evgeny P.; Timoshenko, Roman V.; Kolmogorov, Vasilii S.; Erofeev, Alexander S.; Gorelkin, Petr V.; Mitkevich, Vladimir A.; Makarov, Alexander A. (Frontiers in Molecular Neuroscience, 2024)
Post-translational modifications of beta-amyloid (Aβ) play an important role in the pathogenesis of Alzheimer’s disease (AD). Aβ modifications such as Ser8 phosphorylation (pS8-Aβ42) and Asp7 isomerization (iso-Aβ42) can significantly alter the properties of Aβ and have been detected in vivo. One of the reasons for the different pathogenicity of Aβ isoforms may be the activation of different signaling cascades leading to changes in the mechanical properties of cells. In this paper, we used correlative scanning ion-conductance microscopy (SICM) and Pt-nanoelectrodes to compare the effects of Aβ isoforms on the Young’s modulus of SH-SY5Y cells and the level of ROS. It was found that unmodified Aβ42 resulted in the largest increase in cell Young’s modulus of all isoforms after 4 h of incubation, while pS8-Aβ42 induced the greatest increase in stiffness and ROS levels after 24 h of incubation. Analysis of signaling proteins involved in the regulation of the actin cytoskeleton showed that Aβ42, pS8-Aβ42 and iso-Aβ42 have different effects on cofilin, GSK3β, LIMK, ERK and p38. This indicates that post-translational modifications of Aβ modulate its effect on neuronal cells through the activation of various signaling cascades, which affects the mechanical properties of cells.